Simultaneous stenting of the left main coronary stem and internal carotid artery in a hemodynamically unstable patient - Sagić Dragan; Antonić Želimir; Stanišić Milan M.; Ilijevski Nenad; Milojević Predrag; Mašulović Dragan; Radak Đorđe (Vojnosanitetski Pregled)
Introduction. Combined endovascular interventions on carotid and coronary arteries are rare. Stenting of the unprotected coronary left main stem is a high risk procedure. We presented hemodynamically unstable patient with combined carotid artery and left main stem coronary artery stenting. Case report. A 78-year-old female patient was admitted to our institution for right carotid endaterectomy. The patient had 80% stenosis of the right carotid artery and occlusion of the left carotid artery. Coronary angiography revealed 70% ostial left main stenosis, occlusion of the right coronary artery and the left circumflex artery, and 80% stenosis of the left anterior descending artery. Simultaneous carotid artery endaterectomy and coronary artery by-pass grafting were considered. Due to high perioperative risk, surgery was rejected, and the patient was treated endovascularly with stenting of arteries occluded. The procedure was completed without complications and the patient was hemodynamically stabilised. Conclusion. This report illustrates simultaneous coronary and carotid stenting as a successfull lifesaving procedure.